Method for producing amorphous silicon aluminum-containing metal oxide catalyst and use thereof
By using silicon aluminum nitride to coat metal oxide catalysts, the problems of long treatment process of land landfill leachate, high energy consumption and low pollutant removal efficiency in traditional technology are solved, and the effect of efficient removal of carbon/nitrogen-based pollutants and reducing water pollutants concentration is achieved.
Patent Information
- Application Number
- JP2023106287
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-07-12
- Filing Date
- 2023-06-28
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2043-06-28
AI Technical Summary
In the prior art, when dealing with land landfill leachate, traditional biochemical treatment membrane separation technology has problems such as long process, high energy consumption and secondary pollution, and it is difficult to effectively remove polymer macromolecular pollutants.
Silicon-nitride-coated metal oxide catalyst is used to heat-treat the catalyst to form a pore-rich catalyst by activating the metal composite under vacuum drying conditions.
The carbon/nitrogen-based pollutants in the landfill leachate were efficiently removed, and the removal rates of COD and ammonia nitrogen reached 98.3% or above, significantly reducing the concentration of water pollutants after treatment.
Smart Images

Figure 0007659764000001 
Figure 0007659764000002 
Figure 0007659764000003
Abstract
Description
[Technical field]
[0001] The present invention belongs to the field of environmental conservation, and relates to a decomposition-oxidation bifunctional catalyst for aerobic pyrolysis purification of landfill leachate, a manufacturing method thereof, and its use. In particular, the present invention relates to an amorphous silicon aluminum encapsulated metal oxide catalyst for aerobic pyrolysis purification of landfill leachate, which purifies carbon / nitrogen-based pollutants in landfill leachate by the action of the catalyst through a decomposition-oxidation cascade reaction to convert them into inorganic substances such as carbon dioxide, water, and nitrogen. [Background technology]
[0002] Landfill leachate is corrosive, biotoxic and highly pathogenic, and if discharged untreated, it will not only cause environmental pollution, but also harm human life and health. The conventional combined process of "biochemical treatment + membrane separation" has problems such as long flow, high energy consumption, and secondary pollution caused by membrane concentrate, so there is an urgent need to develop a landfill leachate detoxification treatment technology based on chemical reactions that can completely convert the pollutants in the landfill leachate into harmless substances.
[0003] Highly volatile carbon / nitrogen-based pollutants (e.g., fatty acids, ammonia, etc.) in landfill leachate can be converted into environmentally harmless substances by chemical oxidation techniques such as catalytic combustion. However, large molecule pollutants with low volatility cannot be catalytically combusted in the form of gas molecules, and their chemical bonds must be broken to convert them into small molecules that are easily oxidized. China Patent No. 112794571 shows that advanced oxidation technology can realize the oxidative cleavage of chemical bonds of large molecule organic pollutants, forming a cascade process with the biochemical treatment process. However, advanced oxidation technology not only cannot form an independent purification process in practical use, but also cannot be combined with the catalytic combustion process due to the difference in working conditions. China Patent Application Publication No. 107010709 and China Patent Application Publication No. 107099051 propose an aerobic pyrolysis process combining decomposition and oxidation, which is applied in the treatment process of high-concentration organic wastewater and waste resin. However, the main component of the aerobic pyrolysis catalyst is rare earth modified zeolite molecular sieve, and the nanoscale pores of zeolite are unfavorable to the internal mass transfer of large molecular organic pollutants, which reduces the efficiency of the catalytic cracking reaction and leads to carbon deposition. After the organic wastewater is treated in the aerobic pyrolysis reactor, the effluent COD is still as high as 1000mg / L, and it needs to be cascaded with a catalytic oxidation reactor to meet the effluent standard, which increases the purification process flow, operation costs and energy consumption in the process.
[0004] Amorphous silicon aluminum is an important component of industrial catalysts for fluid catalytic cracking, characterized by a rich pore structure and a wide pore size range, which can improve the mass transfer efficiency of large molecular substances, and is mainly used in the pre-crack of heavy components in crude oil. However, the cracking-oxidation bifunctional catalysts manufactured by conventional techniques such as immersion and grinding have defects such as uneven distribution of oxygen vacancies and acidic sites in metal oxide / amorphous silicon aluminum, and aggregation of metal oxide, which are not suitable for the aerobic thermal cracking process characterized by the cracking-oxidation cascade reaction. Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention provides an amorphous silicon aluminum-encapsulated metal oxide catalyst, which has the advantages of highly dispersed acidic sites and oxygen vacancies, a large pore size range, and high mass transfer efficiency, in contrast to the disadvantages of amorphous silicon aluminum-supported metal oxide catalysts, such as uneven distribution of oxygen vacancies and acidic sites, which leads to aggregation of the metal oxide, and a method for producing and using the same.
[0006] The object of the present invention is to provide an amorphous silicon aluminum-encapsulated metal oxide catalyst (MO) having a highly dispersed and abundant pore structure in which acid sites and oxygen vacancies are highly dispersed. x @SiO 2 -Al 2 O 3 ) [Means for solving the problem]
[0007] The method for producing the amorphous silicon aluminum encapsulated metal oxide catalyst includes the steps of: The metal complex is placed in a vacuum drying apparatus and activated at a temperature of 80-120°C and a vacuum of 15-25 Pa for 4-6 hours. The metal complex is then immersed in a mixed solution of a silicon precursor, an aluminum precursor, an acidic chelating agent, and a hydrolysis inhibitor for 3-4 hours. After immersion, the sample is washed with an alcohol solvent and dried to remove the solvent. The resulting solid is then heat-treated at a high temperature of 500-800°C for 4-6 hours to remove organic components, resulting in a MO complex with a highly dispersed and abundant pore structure in which acid sites and oxygen vacancies are highly dispersed. x @SiO 2 -Al 2 O 3 and obtaining a bifunctional aerobic pyrolysis catalyst.
[0008] In the above-mentioned production method, the metal oxide MO x Fe 2 O 3 , Co 3 O 4 , Cr 2 O 3 , CEO 2 , V 2 O 5 , Mn 2O 3 , CuO.
[0009] In the above method, the metal complex is one of Fe-MIL-101, Fe-MIL-100, Fe-MIL-68, Fe-MIL-100, Cr-MIL-101, Ce-MOF-808, V-MIL-101, V-MIL-68, Mn-MIL-100, and Cu-PCN-222, or The metal complexes are Fe / Cu-MIL-101, Fe / Co-MIL-101, Fe / Mn-MIL-101, V / Cu-MIL-101, Cr / Cu-MIL-101, V / Cr-MIL-101, V / Mn-MIL-101, Fe / Cu-MIL-68, V / Cu-MIL-68, Ce / Cu-MOF- 808 , Ce / V-MOF- 808 , Ce / Mn-MOF- 808 , Ce / Mn-MIL-100, Fe / Cu-MIL-100 and Cu / Mn-PCN-222.
[0010] In the above-mentioned production method, the silicon precursor is one of tetramethoxysilane, tetraethyl silicate, and methyltrimethoxysilane. Preferably, the mass ratio of the silicon precursor to the metal complex is 9:1 to 11.8:1, and the silicon precursor is tetramethoxysilane or tetraethyl silicate.
[0011] In the above preparation method, the aluminum precursor is one of aluminum isopropoxide, aluminum sec-butoxide, and di(sec-butanol)aluminum acetoacetate.
[0012] In some specific embodiments, the mass ratio of the aluminum precursor to the silicon precursor is 0.11:1 to 0.37:1, and the aluminum precursor is aluminum sec-butoxide.
[0013] In the above production method, the acidic chelating agent is one of acetic acid and oxalic acid, and the hydrolysis inhibitor is at least one of ethyl acetoacetate, isopropanol, and sec-butanol.
[0014] In the above preparation method, the mass ratio of the acidic chelating agent to the aluminum precursor is 0.21:1 to 0.63:1, the hydrolysis inhibitors are ethyl acetoacetate and sec-butanol, the mass ratio of the ethyl acetoacetate to the aluminum precursor is 0.1:1 to 0.3:1, and the mass ratio of the sec-butanol to the aluminum precursor is 1.6:1 to 4.7:1.
[0015] In the above production method, the alcohol solvent is one or two of methanol, ethanol, and sec-butanol.
[0016] In the above manufacturing method, amorphous silicon aluminum is used as a standard, and metal oxide MO x The loading is 20-35%. According to the ammonia temperature-programmed desorption method, the acid amount of the bifunctional aerobic pyrolysis catalyst is 2.3-4.5mmol / g, and the hydrogen consumption of the oxidation active component is 8.5-17.5mmol / g. The pore volume of the bifunctional aerobic pyrolysis catalyst is 0.8-1.7 cm 3 / g, and the mesopore size range is 2.2 to 18.5 nm.
[0017] The amorphous silicon aluminum doped metal oxide catalyst is produced by the above method.
[0018] In the technical solution of the present invention, the use of the amorphous silicon aluminum doped metal oxide catalyst prepared by the above preparation method for the aerobic pyrolysis purification of landfill leachate is more preferably such that the catalyst converts carbon / nitrogen-based pollutants in the landfill leachate into carbon dioxide, water and nitrogen through a decomposition-oxidation cascade reaction.
[0019] Furthermore, the aerobic pyrolysis purification reaction of the landfill leachate is carried out in a circulating fluidized bed reactor, and both air and landfill leachate are supplied from the bottom of the aerobic pyrolysis reactor; Furthermore, the landfill leachate COD concentration is 1000 to 100000 mg / L, the ammonia nitrogen concentration is 500 to 5000 mg / L, and the reaction pressure is 0.1 to 0.2 MPa (gauge pressure); Further, the contact reaction temperature is 250 to 450°C, and preferably, the contact reaction temperature is 300 to 400°C. Furthermore, the molar ratio of oxygen to landfill leachate is 0.1 to 5, preferably 1.25 to 3; Furthermore, the space velocity is 0.5 to 3.5 h -1 and preferably 1 to 2.5 h -1 It is. Effect of the Invention
[0020] The beneficial effects of the present invention are as follows:
[0021] MO produced by the present invention x @SiO 2 -Al 2 O 3 The catalyst has dual active catalytic sites of highly dispersed acid sites and oxygen vacancies, a rich pore structure and a large pore size range, which enhances the mass transfer process of reactants within the catalyst and increases the efficiency of the decomposition-oxidation cascade reaction.
[0022] MO produced by the present invention x @SiO 2 -Al 2 O 3 In the aerobic pyrolysis purification process of landfill leachate, the catalyst can achieve a COD removal rate of 98.3% or more in landfill leachate, ammonia nitrogen removal rate of 98.0% or more, and a COD concentration of the effluent from aerobic pyrolysis purification can be less than 98.7 mg / L and ammonia nitrogen concentration of less than 24.9 mg / L. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] The present invention will now be further described with reference to the following examples.
[0024] Example 1 30 mg of single metal complex Fe-MIL-101 (Shanghai Kaishu Chemical Technology Co., Ltd., MIL-101(Fe)) was activated at 100°C for 5 h in a vacuum apparatus with a vacuum degree of 20 Pa, and then immersed in a mixture of 300 μL (300 mg) of silicon precursor tetramethoxysilane, 20 μL (20.9 mg) of acidic chelating agent acetic acid, 10 μL (10.3 mg) of hydrolysis inhibitor ethyl acetoacetate, and aluminum precursor (aluminum sec-butoxide / sec-butanol 0.099 g / 150 μL, 0.0495 g / 150 μL, and 0.033 g / 150 μL). After immersion for 3 h, the samples were centrifuged and washed three times with 10 mL of sec-butanol and 10 mL of methanol, and then vacuum dried at 80 °C for 12 h. The obtained samples were SiAl-1@MIL-101, SiAl-2@MIL-101, and SiAl-3@MIL-101, respectively.
[0025] The samples were placed in a tubular furnace and heated to 600°C at a rate of 5°C / min in an air atmosphere and held at that temperature for 2 h. The resulting bifunctional catalysts were 2 O 3 @SiO 2 -Al 2 O 3 -1, Fe 2 O 3 @SiO 2 -Al 2 O 3 -2 and Fe 2 O 3 @SiO 2 -Al 2 O 3 It is -3.
[0026] Fe 2 O 3 @SiO 2 -Al 2 O 3 -1, Fe 2 O 3 @SiO 2 -Al 2 O 3-2 and Fe 2 O 3 @SiO 2 -Al 2 O 3 The acid amounts of the catalysts produced by the ammonia-temperature programmed desorption method for Fe-3 were measured and found to be 4.5, 3.2, and 2.9 mmol / g, respectively. 2 O 3 @SiO 2 -Al 2 O 3 -1, Fe 2 O 3 @SiO 2 -Al 2 O 3 -2 and Fe 2 O 3 @SiO 2 -Al 2 O 3 The hydrogen consumption of the catalysts for Catalyst 3 was measured by the hydrogen-temperature programmed reduction method and found to be 17.5, 14.8 and 11.5 mmol / g, respectively, and the pore volumes of the catalysts were 1.7, 1.3 and 0.8 cm, respectively. 3 / g, with a corresponding pore size range of 2.2 to 18.5 nm.
[0027] The catalyst performance test was carried out in a three-stage temperature-controlled fluidized bed steel reactor, and the landfill leachate COD concentration was 8327 mg / L and the ammonia nitrogen concentration was 1263 mg / L. The landfill leachate was purified by aerobic pyrolysis using the manufactured bifunctional catalyst with different silicon-aluminum mass ratios. The catalyst was filled into the aerobic pyrolysis reactor, and the landfill leachate was pumped into the reactor by a peristaltic pump. The reaction conditions were reaction pressure (gauge pressure) 0.1 MPa, reaction temperature 350°C, oxygen to landfill leachate feed molar ratio 2.3, and space velocity 1.5 h -1 The COD removal rate and concentration, ammonia nitrogen removal rate and concentration, and non-methane total hydrocarbon concentration in the landfill leachate are shown in Table 1.
[0028] [Table 1]
[0029] The mass ratio of aluminum precursor to silicon precursor is 33% Fe 2 O 3 @SiO 2 -Al 2 O 3 The catalyst has the highest removal rate of COD and ammonia nitrogen in landfill leachate, and the purified effluent COD and ammonia nitrogen concentrations are 8.3 and 6.9 mg / L, respectively.
[0030] Example 2 The Fe-MIL-101 after activation under the conditions of Example 1 was Case 1 with 300 μL (300 mg) of silicon precursor tetramethoxysilane and aluminum precursor aluminum isopropoxide / sec-butanol (0.099 g of aluminum isopropoxide dispersed in 150 μL of sec-butanol); Case 2 with 300 μL (354 mg) of silicon precursor tetraethyl silicate and aluminum precursor aluminum isopropoxide / isopropanol (0.099 g of aluminum isopropoxide dispersed in 150 μL of isopropanol); Case 3 with 300 μL (270 mg) of silicon precursor methyltrimethoxysilane and aluminum precursor di(sec-butanol)aluminum acetoacetate / sec-butanol (0.099 g of di(sec-butanol)aluminum acetoacetate dispersed in 150 μL of sec-butanol); The catalysts were prepared in the same manner as in Example 1, except that the catalysts were soaked in a mixed solution of silicon precursors of different cases, aluminum precursors, and some hydrolysis inhibitors. 2 O 3 @SiO 2 -Al 2 O 3 -4, Fe 2 O 3 @SiO 2 -Al 2 O 3 -5, Fe 2 O 3 @SiO 2 -Al 2O 3 It is -6.
[0031] Fe 2 O 3 @SiO 2 -Al 2 O 3 -4, Fe 2 O 3 @SiO 2 -Al 2 O 3 -5, Fe 2 O 3 @SiO 2 -Al 2 O 3 The acid amounts of the catalysts produced by the ammonia temperature programmed desorption method for Fe-6 were measured and found to be 4.5, 4.1 and 3.7 mmol / g, respectively. 2 O 3 @SiO 2 -Al 2 O 3 -4, Fe 2 O 3 @SiO 2 -Al 2 O 3 -5, Fe 2 O 3 @SiO 2 -Al 2 O 3 The hydrogen consumption of the catalysts for Catalyst 6 was measured by the hydrogen-temperature programmed reduction method, and was found to be 16.9, 15.6, and 13.5 mmol / g, respectively, and the pore volumes of the catalysts were 1.7, 1.5, and 1.5 cm, respectively. 3 / g, with a corresponding pore size range of 2.2 to 18.5 nm.
[0032] The performance test of the catalyst is carried out according to Example 1, and the selected landfill leachate COD concentration is 51422 mg / L, and the ammonia nitrogen concentration is 964 mg / L. The COD removal rate, concentration, and ammonia nitrogen removal rate, concentration, and non-methane total hydrocarbon concentration in the landfill leachate are shown in Table 2.
[0033] [Table 2]
[0034] The catalyst prepared using tetramethoxysilane as silicon precursor and aluminum sec-butoxide as silicon aluminum precursor had the highest removal rates of COD and ammonia nitrogen from landfill leachate, which were 99.9% and 99.2%, respectively.
[0035] Example 3 The single metal complex is designated V-MIL-101 (MIL-101(V)). The activation conditions are divided into three cases: Case 1: Activation in a vacuum chamber at 15 Pa for 6 hours at 100°C. Case 2: Activation at 100℃ for 6 hours in a vacuum chamber of 20 Pa. Case 3: Activation in a vacuum chamber at 25 Pa for 6 hours at 100°C. The other conditions are the same as those in the first embodiment.
[0036] The bifunctional catalysts produced were V 2 O 5 @SiO 2 -Al 2 O 3 -15, V 2 O 5 @SiO 2 -Al 2 O 3 -20, V 2 O 5 @SiO 2 -Al 2 O 3 -25, and the performance test of the catalyst is carried out according to Example 1. The COD removal rate, concentration, ammonia nitrogen removal rate, concentration, and non-methane total hydrocarbon concentration in the landfill leachate are shown in Table 3.
[0037] [Table 3]
[0038] Example 4 The conditions were the same as in Example 1, except that the amounts of the acidic chelating agents used were changed to 30 μL (31.4 mg) and 40 μL (41.8 mg), respectively.
[0039] The prepared bifunctional catalysts were Fe 2 O 3 @SiO 2 -Al 2 O 3 -30 (the amount of acidic chelating agent used was 30 μL) and Fe 2 O 3 @SiO 2 -Al 2 O 3 The acid amounts of the catalysts produced were 3.1 and 2.3 mmol / g, respectively, the hydrogen consumptions of the catalysts were 11.6 and 8.5 mmol / g, and the pore volumes of the catalysts were 1.3 and 0.8 cm3, respectively. 3 / g, and the corresponding pore size range is 3.6-18.5 nm. The performance test of the catalyst is carried out according to Example 1, and the selected landfill leachate COD concentration is 5186 mg / L, and the ammonia nitrogen concentration is 2045 mg / L. The COD removal rate, concentration, and ammonia nitrogen removal rate, concentration, and non-methane total hydrocarbon concentration in the landfill leachate are shown in Table 4.
[0040] [Table 4]
[0041] When the amount of the acidic chelating agent was 30 μL, the bifunctional catalyst had the highest purification efficiency for organic pollutants and ammonia nitrogen-based substances in landfill leachate. The effluent COD and ammonia nitrogen concentrations of the aerobic pyrolysis purification were 49.9 mg / L and 12.3 mg / L, respectively, and the non-methane total hydrocarbons were 28.2 mg / m 3 It is.
[0042] Example 5 The same procedure as in Example 1 was repeated except that the single metal complex Fe-MIL-101 was changed to the single metal complexes Fe-MIL-100 (MIL-100(Fe)), Fe-MIL-68 (MIL-68(Fe)), Cr-MIL-101 (MIL-101(Cr)), Ce-MOF-808 (MOF-808(Zr)), V-MIL-101, Mn-MIL-100, and Cu-PCN-222 (PCN-222(Cu)). The bifunctional catalysts produced were Fe 2 O 3 @SiO 2 -Al 2 O 3 -7, Fe 2 O 3 @SiO 2 -Al 2 O 3 -8, Cr 2 O 3 @SiO 2 -Al 2 O 3 , CEO 2 @SiO 2 -Al 2 O 3 , V 2 O 5 @SiO 2 -Al 2 O 3 , Mn 2 O 3 @SiO 2 -Al 2 O 3 and CuO@SiO 2 -Al 2 O 3 It is.
[0043] The COD concentration of the landfill leachate was 8327 mg / L, and the ammonia nitrogen concentration was 1263 mg / L. The catalyst performance test was carried out according to Example 1, and the COD removal rate, concentration, ammonia nitrogen removal rate, concentration, and total non-methane hydrocarbon concentration in the landfill leachate are shown in Table 5.
[0044] [Table 5A]
[0045] The catalyst containing amorphous silicon aluminum with the selected single metal complex has a COD removal rate of 98.8% or more and ammonia nitrogen removal rate of 98.1% or more in landfill leachate.
[0046] Example 6 The procedure is the same as in Example 1, except that the single metal complex Fe-MIL-101 is changed to the bimetallic complexes Fe / Cu-MIL-101, Fe / Co-MIL-101, Fe / Mn-MIL-101, V / Cu-MIL-101, Cr / Cu-MIL-101, V / Cr-MIL-101, V / Mn-MIL-101, Fe / Cu-MIL-68, V / Cu-MIL-68, Ce / Cu-MOF-808, Ce / V-MOF-808, Ce / Mn-MOF-808, Ce / Mn-MIL-100, Fe / Cu-MIL-100 and Cu / Mn-PCN-222.
[0047] The method for producing the MIL-101 type bimetallic complex is to dissolve 1.66 g of terephthalic acid, metal 1 (see the table below for type and amount used), and metal 2 (see the table below for type and amount used) in 150 mL of N,N-dimethylformamide solution, react them in a thermostatic oven at 110°C for 30 hours, and after the reaction is complete, filter and wash the bimetallic complex with 300 mL of N,N-dimethylformamide and 300 mL of acetone, then vacuum dry at 80°C. The obtained sample is Fe / Cu-MIL-101.
[0048] [Table 5B]
[0049] The method for producing the MIL-68 type bimetallic complex is the same as that for producing the MIL-101 type bimetallic complex, except that the reaction temperature is 180°C.
[0050] [Table 5C]
[0051] The method for producing the MOF-808 type bimetallic complex is the same as that for producing the MIL-101 type bimetallic complex, except that terephthalic acid is replaced with trimesic acid and the reaction time is changed to 2 hours.
[0052] [Table 5D]
[0053] The method for producing the MIL-100 type bimetallic complex is the same as that for producing the MIL-101 type bimetallic complex, except that terephthalic acid is replaced with trimesic acid.
[0054] [Table 5E]
[0055] The method for producing the PCN-222 type bimetallic complex is the same as the MIL-101 type, except that terephthalic acid is replaced with porphyrin and the reaction temperature is 100°C.
[0056] [Table 5F]
[0057] The bifunctional catalysts thus prepared were Fe 2 O 3 -CuO@SiO 2 -Al 2 O 3 -1, Fe 2 O 3 -Co 3 O 4 @SiO 2 -Al 2 O 3 , Fe 2 O 3 -Mn 2 O 3 @SiO 2 -Al 2 O 3 , V 2 O 5 -CuO@SiO 2-Al 2 O 3 -1, Cr 2 O 3 -CuO@SiO 2 -Al 2 O 3 、V 2 O 5 -Cr 2 O 3 @SiO 2 -Al 2 O 3 、V 2 O 5 -Mn 2 O 3 @SiO 2 -Al 2 O 3 、Fe 2 O 3 -CuO@SiO 2 -Al 2 O 3 -2、V 2 O 5 -CuO@SiO 2 -Al 2 O 3 -2、CeO 2 -CuO@SiO 2 -Al 2 O 3 、CeO 2 -V 2 O 5 @SiO 2 -Al 2 O 3 、CeO 2 -Mn 2 O 3 @SiO 2 -Al 2 O 3 、Fe 2 O 3 -CuO@SiO 2 -Al 2 O 3 -3 and CuO-Mn 2 O 3 @SiO 2 -Al 2 O 3 It becomes like this.
[0058] The COD concentration of the landfill leachate was 8327 mg / L, and the ammonia nitrogen concentration was 1263 mg / L. The catalyst performance test was carried out according to Example 1, and the COD removal rate, concentration, ammonia nitrogen removal rate, concentration, and total non-methane hydrocarbon concentration in the landfill leachate are shown in Table 6.
[0059] [Table 6]
[0060] The catalyst containing amorphous silicon aluminum with the selected bimetallic complex has a COD removal rate of more than 99.8% and ammonia nitrogen removal rate of more than 98.1% in landfill leachate.
[0061] Example 7 The landfill leachates generated at different landfill stages were selected. LL-1 had a COD concentration of 8327 mg / L and an ammonia nitrogen concentration of 1263 mg / L, LL-2 had a COD concentration of 42064 mg / L and an ammonia nitrogen concentration of 853 mg / L, and LL-3 had a COD concentration of 78426 mg / L and an ammonia nitrogen concentration of 692 mg / L. The catalyst Fe prepared in Example 1 was used to measure the leachate concentration. 2 O 3 @SiO 2 -Al 2 O 3 The reaction conditions were: reaction pressure 0.2MPa, reaction temperature 350℃, oxygen to landfill leachate feed molar ratio 2.3, space velocity 1.5h -1 The COD removal rate and concentration, ammonia nitrogen removal rate and concentration, and total non-methane hydrocarbon concentration in the landfill leachate are shown in Table 7.
[0062] [Table 7]
[0063] Fe 2 O 3 @SiO 2 -Al 2 O 3-1 The bifunctional catalyst has a COD removal rate of more than 99.9% and ammonia nitrogen removal rate of more than 99.0% in the leachate.
[0064] Example 8 The aerobic pyrolysis treatment process of landfill leachate is also affected by the aerobic pyrolysis reaction temperature. 2 O 3 @SiO 2 -Al 2 O 3 -1 is adopted, the landfill leachate sample in Example 1 is selected, and the aerobic pyrolysis reaction temperature is changed according to the feed molar ratio of oxygen and landfill leachate and the space velocity in the catalytic performance test in Example 3. The COD removal rate, concentration, ammonia nitrogen removal rate, concentration, and non-methane total hydrocarbon concentration in the landfill leachate are shown in Table 8.
[0065] [Table 8]
[0066] When the reaction temperature is 350°C, the removal efficiency of organic pollutants in landfill leachate is highest.
[0067] Example 9 The aerobic pyrolysis treatment process of landfill leachate is also affected by the molar ratio of oxygen and landfill leachate fed during the aerobic pyrolysis process. 2 O 3 @SiO 2 -Al 2 O 3 -1 is adopted, the landfill leachate sample in Example 1 is selected, and the molar ratio of oxygen and landfill leachate is changed according to the reaction temperature and space velocity in the catalytic performance test in Example 1. The COD removal rate, concentration, ammonia nitrogen removal rate, concentration, and non-methane total hydrocarbon concentration in the landfill leachate are shown in Table 9.
[0068] [Table 9]
[0069] When the supply molar ratio of oxygen to landfill leachate is 2.3, the purification efficiency of landfill leachate is the highest, and the purified water COD concentration and ammonia nitrogen concentration are 7.4 and 7.7 mg / L, respectively.
[0070] Example 10 Catalyst Fe prepared in Example 1 2 O 3 @SiO 2 -Al 2 O 3 The catalyst stability test was carried out by adopting Catalyst 1-1 according to Example 1. The leachate aerobic pyrolysis purification device was operated stably for 100 hours, and no obvious deactivation phenomenon was observed in the catalyst. The catalyst has an extremely high purification effect on organic pollutants in the landfill leachate, and the catalyst stability also reaches 100 hours.
[0071] Comparative Example 1 1.6875g of ferric chloride hexahydrate was completely dissolved in 20mL of deionized water, and after dissolution, 9.5g of HY molecular sieve with a silicon-aluminum ratio of 5:1 was added and stirred for 12h. The mixture was then placed in a 100℃ oil bath and slowly dehydrated by stirring. The mixture was then placed in a tubular furnace and heated to 600℃ at 5℃ / min in an air atmosphere for 3h. The catalyst was Fe 2 O 3 The catalyst performance test was carried out in a three-stage temperature-controlled fluidized bed steel reactor, the COD concentration of the landfill leachate was 8327mg / L, and the ammonia nitrogen concentration was 1263mg / L. The bifunctional catalyst produced by the above method was used to purify the landfill leachate by aerobic pyrolysis, the catalyst was filled in a fluidized bed reactor tube, and the landfill leachate was pumped into the reactor by a peristaltic pump. The reaction conditions were reaction temperature 350℃, molar ratio of oxygen to landfill leachate 2.3, and space velocity 1.5h -1 The COD removal rate is 92.1%, the ammonia nitrogen removal rate is 79.5%, the effluent COD concentration is high at 657.8mg / L, and the ammonia nitrogen concentration is high at 258.9mg / L, which do not meet the wastewater standards. The long-term stability effect of the purification reaction is low, and after only 22 hours of maintenance, obvious catalyst deactivation phenomenon is observed, and the catalyst efficiency is greatly reduced.
[0072] Comparative Example 2 1.1419g of cerium nitrate hexahydrate was completely dissolved in 20mL of deionized water. After dissolution, 9.5g of amorphous silicon aluminum with a silicon-aluminum ratio of 5:1 was added and stirred for 12 hours. The mixture was then placed in a 100°C oil bath and slowly dehydrated by stirring. The mixture was then placed in a tubular furnace and heated to 600°C at a rate of 5°C / min in an air atmosphere for 3 hours. The catalyst was CeO 2 / SiO 2 -Al 2 O 3 When leachate was purified under the process conditions of Comparative Example 1, the COD concentration removal rate was 94.6%, the ammonia nitrogen removal rate was 81.3%, the effluent COD concentration was high at 449.7 mg / L, the ammonia nitrogen concentration was high at 236.2 mg / L, and the long-term stability of the purification reaction was slightly improved compared to the catalyst prepared in Comparative Example 1, but after only 42 hours of maintenance, obvious catalyst deactivation phenomenon was observed, and the catalyst efficiency was significantly reduced.
Claims
1. The metal complex is placed in a vacuum drying apparatus and activated at a temperature of 80-120°C and a vacuum of 15-25 Pa for 4-6 hours, followed by immersion in a mixed solution of a silicon precursor, an aluminum precursor, an acidic chelating agent, and a hydrolysis inhibitor for 3-4 hours; the sample after immersion is washed with an alcohol solvent, dried to remove the solvent, and the resulting solid is heat-treated at a high temperature of 500-800°C for 4-6 hours to remove organic components, to obtain MOI having an acid content of 2.3-4.5 mmol / g and a pore volume of 0.8-1.7 cm3 / g. x @SiO 2 -Al 2 O 3 Obtaining a bifunctional aerobic pyrolysis catalyst; The metal oxide MOx is one or two of Fe2O3, Co3O4, Cr2O3, CeO2, V2O5, Mn2O3, and CuO. A method for producing an amorphous silicon aluminum encapsulated metal oxide catalyst.
2. The method for producing an amorphous silicon aluminum doped metal oxide catalyst according to claim 1, wherein the metal complex is one of MIL-101, MIL-100, MIL-68, MOF-808, and PCN-222 crystal structures.
3. The method for producing an amorphous silicon aluminum encapsulated metal oxide catalyst according to claim 2, wherein the metal complex is one of Fe-MIL-101, Fe-MIL-68, Fe-MIL-100, Cr-MIL-101, Ce-MOF-808, V-MIL-101, V-MIL-68, Mn-MIL-100, and Cu-PCN-222.
4. 3. The method for producing an amorphous silicon aluminum encapsulated metal oxide catalyst according to claim 2, wherein the metal complex is one of Fe / Cu-MIL-101, Fe / Co-MIL-101, Fe / Mn-MIL-101, V / Cu-MIL-101, Cr / Cu-MIL-101, V / Cr-MIL-101, V / Mn-MIL-101, Fe / Cu-MIL-68, V / Cu-MIL-68, Ce / Cu-MOF-808, Ce / V-MOF-808, Ce / Mn-MOF-808, Ce / Mn-MIL-100, Fe / Cu-MIL-100 and Cu / Mn-PCN-222.
5. 2. The method for producing an amorphous silicon aluminum encapsulated metal oxide catalyst according to claim 1, wherein the silicon precursor is one of tetramethoxysilane, tetraethyl silicate, and methyltrimethoxysilane.
6. The method for producing an amorphous silicon aluminum encapsulated metal oxide catalyst according to claim 5, characterized in that the mass ratio of the silicon precursor to the metal complex is 9:1 to 11.8:1, and the silicon precursor is tetramethoxysilane, tetraethyl silicate.
7. The method for producing an amorphous silicon aluminum-encapsulated metal oxide catalyst according to claim 1, wherein the aluminum precursor is one of aluminum isopropoxide, aluminum sec-butoxide, and di(sec-butanol)aluminum acetoacetate, and the mass ratio of the aluminum precursor to the silicon precursor is 0.11:1 to 0.37:
1.
8. 2. The method for producing an amorphous silicon aluminum encapsulated metal oxide catalyst according to claim 1, wherein the acidic chelating agent is one of acetic acid and oxalic acid, the hydrolysis inhibitor is ethyl acetoacetate and an alcohol, and the alcohol is isopropanol or sec-butanol.
9. The method for producing an amorphous silicon aluminum encapsulated metal oxide catalyst according to claim 8, wherein the mass ratio of the ethyl acetoacetate to the aluminum precursor is 0.1:1 to 0.3:1, and the mass ratio of the alcohol to the aluminum precursor is 1.6:1 to 4.7:
1.
10. the mass ratio of the acidic chelating agent to the aluminum precursor is 0.21:1 to 0.63:1; 2. The method for producing an amorphous silicon aluminum encapsulated metal oxide catalyst according to claim 1, wherein the alcohol solvent is one or two of methanol, ethanol, and sec-butanol.
11. Based on amorphous silicon aluminum, metal oxide MO x The loading amount is 20 to 35%. The hydrogen consumption of the oxidation active component of the amorphous silicon aluminum encapsulated metal oxide catalyst is 8.5 to 17.5 mmol / g; 2. The method for producing an amorphous silicon aluminum encapsulated metal oxide catalyst according to claim 1, wherein the mesopore size range of the catalyst is 2.2 to 18.5 nm.
12. 2. Use of the amorphous silicon aluminum doped metal oxide catalyst produced by the method according to claim 1 for the aerobic pyrolysis purification of landfill leachate.
13. The use according to claim 12, wherein the catalyst converts carbon / nitrogen based pollutants in landfill leachate into carbon dioxide, water and nitrogen by a decomposition-oxidation cascade reaction.
14. The aerobic pyrolysis purification reaction of the landfill leachate is carried out in a circulating fluidized bed reactor, and air and the landfill leachate are both supplied from the bottom of the aerobic pyrolysis reactor; The catalytic reaction temperature is 250 to 450°C. The molar ratio of oxygen to landfill leachate is 0.1 to 5; Space velocity is 0.5 to 3.5 h -1 The use according to claim 12, characterized in that
15. The use according to claim 14, characterized in that the COD concentration of the landfill leachate is 1000-100000 mg / L, the ammonia nitrogen concentration is 500-5000 mg / L, and the reaction pressure is 0.1-0.2 MPa.
16. The use according to claim 14, characterized in that the contact reaction temperature is 300-400°C.
17. The use according to claim 14, characterized in that the molar ratio of oxygen to landfill leachate is between 1.25 and 3.
18. The space velocity is 1 to 2.5 h -1 15. The use according to claim 14, characterized in that
Citation Information
Patent Citations
Production of dual function catalyst
JP1994198177A
Catalyst for water treatment and treatment of water
JP1998174882A
Method for the preparation of highly homogeneous amorphous silica-alumina compositions
JP2006505404A
Porous complex composite and production method of same
JP2017149667A
Catalyst and method for its preparation, and method for preparing isobutylene by utilizing said catalyst
JP2017537781A